The Role of Al-Mizan by Al-Ghazali in Fraud Prevention - Aziz, Muhammad El Barony Haidar (ITB AAS INDONESIA Surakarta, 2024)
There are still many cases of fraud in Indonesia and some of them result in significant losses for the country. These fraud phenomena, especially in Indonesia, illustrate the poor ethical practices of accountants as preparers of financial reports. Even though Indonesia already has an Indonesian Code of Ethics for Accountants which regulates the ethics of the accounting profession in Indonesia, there is still a lot of unethical behavior. One assumption is that the loss of ethical behavior is due to the lack of religious values in accountants which results in accountants not being able to differentiate between good and bad. This research, using the library research method, aims to raise the value of religiosity, especially according to Al-Ghazali in his book Mizan al-'Amal-or Al-Mizan, with the ethics of an accountant in complying with a code of ethics and avoiding fraud. In Al-Mizan, Al-Ghazali emphasized that with this connection a person can have more awareness of ethics. Because this will encourage a person to only do things recommended by God, which of course leads to good things such as compliance with regulations and avoids bad actions such as fraud.